The Use of Snakes and Ladders Game as English Teaching Media to Improve Mentally Retarded Students’ Vocabulary - Hariyanti, Niarmi; Tjalla, Maghdahalena; Arqam, Arqam; Dalle, H. Ambo; Sunubi, Abdul Haris (STAIN Majene, 2023)
Mentally retarded students are students who have intellectual disability. Mental disabilities refer to students’ difficulties in understanding sentences, word, and numbers as they have low view. Therefore, they have difficulty to interact with other people, understand the sentences and communicative with others. One technique that is suitable for teaching the vocabulary for mentally retarded students is Snakes and Ladders game. The research is quantitative research. The subject of this research was Junior High School of SLB (Sekolah Luar Biasa) Negeri 1 Pinrang in 2022-2023 academic years consisting of 10 students. In this research there were 10 samples that had mentally retarded. The instrument used in this research was vocabulary test and researcher gives the questionnaire by asking them about the question. The researcher using Snakes and Ladders a media in teaching vocabulary for mentally retarded students. The finding of this research showed the mean score of pre-test was 63.32. While the mean of post-test was 73.56. This showed that there was significant different between pre-test and post-test as the T-test showed the significance values (2-tailed) were 0.000 greater than 0.5. The result of P-value (0.000) was lower than level of significance (alpha (α)=0.05). It means that H1 was accepted. The researcher concludes that: (1) The use of Snakes and Ladders game improve the vocabulary ability of the junior high school of SLB (Sekolah Luar Biasa) negeri 1 Pinrang.; (2) The students gave good respond toward Snakes and Ladders game in learning English Vocabulary. Based on the data analyzed the researcher concluded that the use of Snakes and Ladders game improve the vocabulary ability and gain very good respond from junior high school of SLB (Sekolah Luar Biasa) Negeri 1 Pinrang.